2006
DOI: 10.1200/jco.2006.24.18_suppl.13121
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of UGT1A polymorphisms predictive for pharmacokinetics and treatment outcome in non-small cell lung cancer patients treated with irinotecan and cisplatin

Abstract: 13121 Purpose: To determine whether UGT1A1, UGT1A7, and UGT1A9 polymorphisms affect pharmacokinetics (PK) of irinotecan and treatment outcome of Korean patients with advanced non-small cell lung cancer (NSCLC). Methods: Eighty-one patients with advanced NSCLC were treated with irinotecan and cisplatin chemotherapy. Genomic DNA was extracted from peripheral blood and genotyped using direct sequencing. We analyzed the association of UGT1A genotypes with irinotecan PK and clinical outcomes. Results: In genotype-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(110 citation statements)
references
References 0 publications
8
95
2
5
Order By: Relevance
“…37,38 The UGT1A1*28 polymorphism, which is an insertion of an extra thymine-adenine (TA) repeat in the promoter, is associated with enzyme activity inversely related Acetaminophen, 10 bilirubin, 9 buprenorphine, 14 carvedilol, 16 doxorubicin, 19 ethinylestradiol, 14 entacapone, 20 SN-38, 22 etoposide, 23 ezetimibe, 24 cis-and trans-hydroxytamoxifen, 25 irinotecan, 26 morphine, 27 nalorphine, 14 naltrexone, 14 retigabine, 28 to repeat length. This insertion polymorphism affects the TATA box upstream of UGT1A1, which is responsible for the binding of general transcription factor IID, which plays an given as monotherapy and with other *7 (exon 5) 57 bilirubin level anticancer therapy UGT1A1*28 58 Pharmacokinetic parameters, 20 300 mg/m 2 over 90 min q 3 wks; neutropenia, diarrhea, and (Caucasian) patients encouraged to take ANC loperamide 4 mg at onset of diarrhea UGT1A1*28 65 Drug toxicity, time to 51 63 and 22; patients encouraged to take loperamide 4 mg at onset of diarrhea UGT1A1*28 69 Response rate, drug 42 200 mg/m 2 q 3 wks; regimen included toxicity, survival carboplatin UGT1A1*28, *60, Pharmacokinetic parameters, 81 80 mg/m 2 over 60 min on days 1 and 8; and *6 70 tumor response, drug (Korean) regimen included cisplatin toxicity, delivered dose of irinotecan UGT1A1*28 61 Hematologic and 250 180 mg/m 2 over 120 min; regimen nonhematologic toxicities, (Caucasian) included 5-fluorouracil; diarrhea response rate, survival treated with loperamide 4 mg UGT1A1*28 71 Pharmacokinetic parameters, 62 350 mg/m 2 combined with oral diarrhea, neutropenia neomycin or with placebo for 3 days UGT1A1*28, *27, *6 59 Pharmacokinetic parameters 46 Several dosages in combination; some (Japanese) regimens contained 5-fluorouracil, leucovorin, or cisplatin SNPs in UGT1A7, Pharmacokinetic parameters 84 Several doses studied; given as UGT1A9, and (Japanese) monotherapy and in combination with UGT1A1*28, *27, *6 72 5-fluorouracil, leucovorin, or cisplatin important role in the initiation of transcription. 38 Therefore, individuals who are homozygous for seven TA re...…”
Section: Pharmacogenetics Of Ugt1a1mentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 The UGT1A1*28 polymorphism, which is an insertion of an extra thymine-adenine (TA) repeat in the promoter, is associated with enzyme activity inversely related Acetaminophen, 10 bilirubin, 9 buprenorphine, 14 carvedilol, 16 doxorubicin, 19 ethinylestradiol, 14 entacapone, 20 SN-38, 22 etoposide, 23 ezetimibe, 24 cis-and trans-hydroxytamoxifen, 25 irinotecan, 26 morphine, 27 nalorphine, 14 naltrexone, 14 retigabine, 28 to repeat length. This insertion polymorphism affects the TATA box upstream of UGT1A1, which is responsible for the binding of general transcription factor IID, which plays an given as monotherapy and with other *7 (exon 5) 57 bilirubin level anticancer therapy UGT1A1*28 58 Pharmacokinetic parameters, 20 300 mg/m 2 over 90 min q 3 wks; neutropenia, diarrhea, and (Caucasian) patients encouraged to take ANC loperamide 4 mg at onset of diarrhea UGT1A1*28 65 Drug toxicity, time to 51 63 and 22; patients encouraged to take loperamide 4 mg at onset of diarrhea UGT1A1*28 69 Response rate, drug 42 200 mg/m 2 q 3 wks; regimen included toxicity, survival carboplatin UGT1A1*28, *60, Pharmacokinetic parameters, 81 80 mg/m 2 over 60 min on days 1 and 8; and *6 70 tumor response, drug (Korean) regimen included cisplatin toxicity, delivered dose of irinotecan UGT1A1*28 61 Hematologic and 250 180 mg/m 2 over 120 min; regimen nonhematologic toxicities, (Caucasian) included 5-fluorouracil; diarrhea response rate, survival treated with loperamide 4 mg UGT1A1*28 71 Pharmacokinetic parameters, 62 350 mg/m 2 combined with oral diarrhea, neutropenia neomycin or with placebo for 3 days UGT1A1*28, *27, *6 59 Pharmacokinetic parameters 46 Several dosages in combination; some (Japanese) regimens contained 5-fluorouracil, leucovorin, or cisplatin SNPs in UGT1A7, Pharmacokinetic parameters 84 Several doses studied; given as UGT1A9, and (Japanese) monotherapy and in combination with UGT1A1*28, *27, *6 72 5-fluorouracil, leucovorin, or cisplatin important role in the initiation of transcription. 38 Therefore, individuals who are homozygous for seven TA re...…”
Section: Pharmacogenetics Of Ugt1a1mentioning
confidence: 99%
“…Table 2 shows representative pharmacogenetic clinical trials of UGT1A1 and irinotecan. 48,49,[57][58][59][60][61][62][63][64][65][67][68][69][70][71][72][73][74][75][76][77][78][79] In what is considered the first prospective trial of irinotecan pharmacogenetics, an association was shown between UGT1A1*28 and decreased SN-38 glucuronidation rate. 58 This study was 78 drug toxicity (Chinese and Malay) UGT1A1*28 79 Drug toxicity 20 Several dosages; given as monotherapy and amended to increase the dose of irinotecan to 350 mg/m 2 .…”
Section: Irinotecan and Ugt1a1mentioning
confidence: 99%
“…Genetic factors have been shown to play a role in drug disposition and effects. [3][4][5][6][7][8][9] In particular, polymorphisms in genes involved in metabolism and transport of chemotherapeutic drugs, including ABC transporters, are likely to affect response to therapy. Expression of the ATP-binding cassette (ABC) multidrug transporters has been implicated in tumor cell resistance to anticancer therapy, altered clearance of chemotherapy drugs, and associated toxicity.…”
mentioning
confidence: 99%
“…29 Although no statistical association of UGT1A1 * 6 with the occurrence of severe toxicity was observed in our study, a recent report showed that UGT1A1 * 6 played a functionally important role for SN-38 glucuronidation and severe toxicity of irinotecan. 31 A variant UGT1A1 * 60, which exists in the phenobarbital-responsive enhancer module of the UGT1A1 promoter region about 3 kb upstream of the TATA box, is associated with the decreased transcriptional activity. 32 In an additional study of Japanese cancer patients, those having homozygous UGT1A1 * 60 were more likely to experience severe adverse reaction to irinotecan.…”
Section: Ugt1a1 Gene Polymorphisms Other Than Ugt1a1 * 28 and Irinotementioning
confidence: 99%
“…In addition to UGT1A1, UGT1A7 and UGT1A9 have been reported to play some roles in glucuronidation of SN-38, and an association between genetic polymorphisms of UGT1A7 (UGT1A7 * 2 and UGT1A7 * 3) and UGT1A9 (UGT1A9 * 3, UGT1A9 * 5, and UGT1A9 * 22) genes and irinotecan toxicity has been demonstrated in several groups. 31,[34][35][36] However, the results were controversial and the role of these variants in irinotecan toxicity remains to be clarified. In addition, there is a linkage disequilibrium among these variants including UGT1A1.…”
Section: Ugt1a1 Gene Polymorphisms Other Than Ugt1a1 * 28 and Irinotementioning
confidence: 99%